2020
DOI: 10.3889/oamjms.2020.5226
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Farmers and Work Fatigue: A Mixed-Method Approach

Abstract: BACKGROUND: In Indonesia, particularly in the coastal area, there is a growing number of seaweed farmers who work in the informal sector as a home-based industry. It is generally assumed that this sub-group of workers is also experiencing work fatigue. AIM: This research aims to explore information-related factors that are associated with fatigue among seaweed workers. METHODS: The study was conducted in Takalar Regency, South Sulawesi, Indonesia. The research used a mixed-method design combining q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The longer a person works, the the feeling of beiing familiar with the work will affect the level of endurance to the fatigue they experience. [15] The statistical test results obtained p value = 0.027, which means that there is a relationship between the years of service and the quality of life on the Air Traffic Controller (ATC) at AirNav Surabaya.…”
Section: Surabayamentioning
confidence: 98%
“…The longer a person works, the the feeling of beiing familiar with the work will affect the level of endurance to the fatigue they experience. [15] The statistical test results obtained p value = 0.027, which means that there is a relationship between the years of service and the quality of life on the Air Traffic Controller (ATC) at AirNav Surabaya.…”
Section: Surabayamentioning
confidence: 98%
“…On land it has been shown that farmers tend to be 'eco-inefficient' 68 , and while they do factor in environmental considerations when it comes to farm management, they tend to prioritise financial concerns and business practices 69 . This is especially true for farmers in labour-intensive farming types 70 , and may hold true in many parts of the world where seaweed farming is also labour-intensive [71][72][73] .…”
Section: Achieving Holistic Kelp Farmingmentioning
confidence: 99%
“…According to Thamrin et al (2020), seaweed farmers usually worked more than eight hours a day. Works are done manually and repetitively.…”
Section: Covid-19 Pandemic Impacts On Economymentioning
confidence: 99%